The Implementation of the Muhadatsah Strategy in Developing Students’ Arabic Speaking Skills - Baiq Mikyal Zahraturrahmah Rahman (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to describe the implementation of the Muhadatsah strategy in developing students’ Arabic speaking skills at Daarul Istikhlas Qur’anic Education Center, Tanak Awu, Central Lombok, West Nusa Tenggara. The main problem addressed in this research is the students’ limited ability and confidence in speaking Arabic during learning activities. The objective of this study is to explain how the Muhadatsah strategy is implemented in Arabic speaking instruction and how it contributes to improving students’ speaking skills. This research employed a descriptive qualitative approach involving one Arabic teacher and students at the institution. Data were collected through classroom observations and interviews. The findings show that the Muhadatsah strategy is implemented through discussion and drilling techniques involving repetitive Arabic conversational practice. Students actively participate in dialogues in pairs and structured group activities, such as two-line speaking practice guided by the class leader or peers. This strategy contributes to the improvement of students’ fluency, grammatical accuracy, and confidence in using Arabic. In addition, the institution provides additional learning support for students who face difficulties, including extra instructional time and supplementary materials. Despite challenges such as limited class time and differences in student proficiency levels, a supportive learning environment plays an important role in the successful implementation of the strategy.